Effects of ibrutinib on in vitro platelet aggregation in blood samples from healthy donors and donors with platelet dysfunction. Issue 1 (1st January 2020) - Ninomoto, Joi; Mokatrin, Ahmad; Kinoshita, Taisei; Marimpietri, Carol; Barrett, Terrance D.; Chang, Betty Y.; Sukbuntherng, Juthamas; James, Danelle F.; Crowther, Mark
ABSTRACT: Background: Ibrutinib, a first-in-class, once-daily inhibitor of Bruton's tyrosine kinase (BTK), is approved in the US and EU for the treatment of various B-cell malignancies. In clinical studies, BTK inhibitors have been associated with increased bleeding risk, which may result from BTK inhibition in platelets. Methods: To better understand the mechanism of ibrutinib in bleeding events, we isolated platelet-rich plasma from healthy donors ( n = 8) and donors with conditions associated with impaired platelet function or with potentially increased bleeding risk (on hemodialysis, taking aspirin, or taking warfarin; n = 8 each cohort) and used light transmission aggregometry to assess platelet aggregation in vitro after exposure to escalating concentrations of ibrutinib, spanning and exceeding the pharmacologic range of clinical exposure. Results: Platelet aggregation was induced by agonists of 5 major platelet receptors: adenosine diphosphate (ADP), thrombin receptor-activating peptide 6 (TRAP6), ristocetin, collagen, or arachidonic acid (AA). Platelet aggregation induced by ADP, TRAP6, ristocetin, and AA was not meaningfully inhibited by the maximal concentrations of ibrutinib (10 µM). In contrast, collagen-induced platelet aggregation was dose-dependently inhibited by ibrutinib in all donor cohorts (maximum aggregation % with 10 μM ibrutinib, −64% to −83% of agonist activity compared to control agonist samples but without ibrutinib). Conclusion: These results confirm prior reports and support a mechanistic role for the inhibition of collagen-induced platelet aggregation in bleeding events among susceptible individuals receiving ibrutinib therapy.